ORGANIZATION OF THE TEXT CREATIONAL ACTIVITIES OF PHILOLOGY SPECIALTIES STUDENTS DURING MORPHOLOGY STUDY - Horokhova, Tetiana (Continuing Professional Education: Theory and Practice, 2019)
Didactic aspects of the organization of the text creational activities of students philologists have been reviewed in the article on the basis of scientific and methodological literature. The aim of the article is to study a system of methods and typology of exercises and tasks to optimize the text creational activities of philology specialties students during morphology study. The article suggest the examples of exercises and tasks which completion develops students’ linguistic alertness, stimulates their linguistic creativity, creates practical skills in self-selecting of texts for study in terms of linguistic norms. Moreover, interactive methods of the text creational activities of students have been considered, which form the ability to work in a team, prepare presentations, use Internet resources, formulate conclusions independently, learn to build texts professionally, work out the tasks etc. The system of exercises and tasks, which has been developed on the basis of developments made by researchers of the theory of the text creational activity, subjects of educational process, has ensured the productive text creational activity of students at various stages of morphological theory learning and also increased their motivation. The peculiarities of educational texts selection for organization of the text creational activities of students have been analyzed. There are such aspects among them as linguistic, professional oriented and linguodidactics. It has been proven in the article that the usage of texts as didactic material during lectures and practical lessons while studying morphology evokes more interest of students than the analyses of separate words, word combinations, sentences, complex syntaxes